HOMESTAY, KOMODIFIKASI DAN PERUBAHAN SOSIAL DI DALAMNYA Studi terhadap penyediaan jasa homestay di Desa Wisata Brayut, Kelurahan Pandowoharjo, Kecamatan Sleman, Kabupaten Sleman, Daerah Istimewa Yogyakarta - , WIJIL ANINDYAJATI; , Drs. Suharman, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Brayut tourism village offers agriculture and Javanese traditional culture as an attraction. Tourist has to stay for a night or longer, so that they can enjoy every tour package(s) as a whole. Therefore, homestay concept implemented, where tourist can stay at local house. There is a commodification of staying overnight in homestay, which include cleanliness and daintiness of homestay, and interaction with locals and reputed as family. Homestay also commodify traditional foods and drinks. Besides giving more value in alternative tourism with simple village atmosphere, homestay also keep money rotation inside Brayut society. With the existence of homestay, tourist are no longer confuse finding place to stay when they take a vacation at Brayut tourism village. Moreover, it is located very close with tourism object, which is inside Brayut village territory. The existence of homestay triggers a more intensive interaction between host, which is local people, and guest, tourists. Inevitably, interaction between two different cultures happens. Way of life inside homestay owner as people of Brayut village, interact with new culture brought by tourists. Interaction between these cultures made a new standard for homestay owner, to have a certain attitude. This standard not formed automatically, but having a connection with environment, including the environment of Brayut, tourism, also public society. Except environment, social process held an important role in a process to form a new standard. Information from all of informants shows that homestay owner tend to involve in a new standard. Their eminent motivation is economy, because when they are not able to get along with the new standard, they are not able to run homestay business. Hence, changes in peopleâs way of life is not as easy as flipping your own hand. It happens on three homestay owner that no longer continue their homestay business, because they are not able to cope with the new standard.